Assessment of antinuclear antibodies (ANA): National recommendations on behalf of the Croatian society of medical biochemistry and laboratory medicine - Tešija Kuna, Andrea (Array, 2021)
Antinuclear antibodies (ANA) represent a family of autoantibodies targeting ubiquitous cellular constituents and are a hallmark of systemic inflammatory autoimmune rheumatic diseases named connective tissue diseases (CTD). The gold standard method for ANA determination is indirect immunofluorescence (IIF) on the human laryngeal epidermoid carcinoma cell line type 2 substrate (HEp-2), but with increasing demand for ANA testing, novel methods eased for automation emerged, which allows testing by staff less experienced in this specific field of laboratory diagnostic. In 2016 The working group (WG) for laboratory diagnostics of autoimmune diseases as part of the Committee for the Scientific Professional Development of the Croatian Society of Medical Biochemistry and Laboratory Medicine (CSMBLM) published the data of a survey regarding general practice in laboratory diagnostics of autoimmune diseases in Croatia. Results indicated high diversity in the performance of autoantibody testing as well as reporting of the results and indicated the need of creating recommendations for the assessment of ANA that would help harmonize diagnostics of systemic autoimmune rheumatic diseases in Croatia. This document encompasses twenty-seven recommendations for ANA testing created concerning indications for ANA testing, preanalytical, analytical, and postanalytical issues, including rational algorithm and quality control assurance. These recommendations are based on the relevant international recommendations and guidelines for the assessment of ANA testing and relevant literature search and should help to harmonize the approach in ANA testing and clarify differences in interpretation of the results obtained using different methods of determination.